Microreactor-based continuous process for controlled synthesis of poly-methyl-methacrylate-methacrylic acid (PMMA) nanoparticles - Dobhal, Anurag; Kulkarni, Amol; Dandekar, Prajakta; Jain, Ratnesh (Journal of Materials Chemistry B, 2017)
We have developed a microreactor-based continuous process for synthesizing PMMA nanoparticles (NPs), based on the principle of nanoprecipitation. Our objective was to identify the critical parameters governing the size of nanoparticles, produced in microreactors, to enable reproducible synthesis of mono-disperse particles. Experiments were carried out in a microreactor, where parameters like flow rates of aqueous and organic phases, residence time and polymer concentrations were varied to examine their influence on particle size and homogeneity. The results from Dynamic Light Scattering confirmed that the particle size decreased with decreasing residence time, whereas when the aqueous to organic phase flow rate ratio was changed sequentially from 9 : 1, 4 : 1, 7 : 3, 3 : 2, to 1 : 1 (v/v), the particle size increased. Particles fabricated using a microreactor demonstrated a narrow and homogenous distribution, thus confirming their monodispersity. TEM, SEM and XRD were also performed for morphology analysis and phase identification of the particles. Further, paclitaxel encapsulated PMMA nanoparticles were prepared using the microreactor, demonstrating an increase in mean size of around 30 nm and a slightly higher polydispersity index compared to the blank nanoparticles. The drug encapsulation efficiency and drug release kinetics of these nanoparticles were comparable to those prepared in batch-experiments, thus establishing the suitability of the technology for preparing drug-loaded nanoparticles. Also, it was observed that at all the residence times (10 min to 10 s), about 80% of the polymer got transformed into nanoparticulate form, thus confirming the efficiency of the microreactor. In recent times, much work has been conducted to synthesize polymeric nanoparticles using different types of microreactors, but they lack detailed investigation of the effect of various parameters on the physiochemical properties of the resulting particles. Our investigation synthesizes PMMA NPs, using microreactor technology, for the very first time, to the best of our knowledge. Furthermore, we have performed a detailed analysis of the influence of various process parameters on the size and uniformity of the resulting nanoparticles. These critical parameters can serve as a useful tool to synthesize a myriad of nanoparticles of alternative polymers, using microreactor technology.